Dampak pembangunan Jalan Balige bypass terhadap alih fungsi lahan Kabupaten Toba - Dian Pranata Tampubolon; Westi Utami; Sutaryono Sutaryono (Universitas Negeri Malang, 2022)
Infrastructure development often has an impact on land use changes. This study aims to map the impact of Balige bypass road construction on land use changes and analyze its suitability with spatial planning. The research method was carried out through descriptive qualitative with a spatial approach. The data includes Sentinel images for 2017 and 2021, maps of the Regional Spatial Plan (RTRW) and interviews with government officials. Image analysis is carried out visually, while mapping of land use changes is carried out through overlaying land use maps for 2017 and 2021 and to map the suitability of the RTRW, overlaying land use maps with the RTRW. The results of the analysis show that after the road construction there was a change in land use from rice fields to settlements covering an area of 103.27 Ha. Meanwhile, an analysis of the RTRW shows that there is a mismatch in the use of a land area of 47.2 Ha. This study shows that the use of remote sensing through sentinel imagery and spatial analysis can be a tool for monitoring natural resources, this study is also useful as material for developing Geography learning.Pembangunan infrastruktur seringkali berdampak pada perubahan penggunaan tanah. Penelitian ini bertujuan memetakan dampak pembangunan jalan Balige bypass terhadap perubahan penggunaan tanah dan menganalisis kesesuaiannya dengan tata ruang. Metode penelitian dilakukan melalui kualitatif deskriptif dengan pendekatan spasial. Data yang digunakan meliputi citra Sentinel tahun 2017 dan 2021, peta Rencana Tata Ruang Wilayah (RTRW) serta wawancara dengan pejabat pemerintahan. Analisis citra dilakukan secara visual, sementara pemetaan perubahan penggunaan tanah dilakukan melalui overlay peta penggunaan tanah 2017 dengan 2021, dan untuk memetakan kesesuaian RTRW dilakukan overlay peta penggunaan tanah dengan RTRW. Hasil analisis menunjukkan pasca pembangunan jalan terjadi perubahan penggunaan tanah dari sawah menjadi pemukiman seluas 103,27 Ha. Sementara analisis terhadap RTRW menunjukkan terjadi ketidaksesuaian penggunaan lahan seluas 47,2 Ha. Kajian ini menunjukkan pemanfaatan penginderaan jauh melalui citra sentinel serta analisis spasial mampu menjadi alat monitoring sumber daya alam, kajian ini juga bermanfaat sebagai bahan pengembangan pembelajaran ilmu Geografi.